CHARACTERISTICS OF EXAMINATIONS CONDUCTED IN CASES OF SUICIDE - M.A. Dekhkkonov; Kh.M. Imomov; Sh.E. Komilov (Western European Studies, 2025)
According to the World Health Organization (WHO), suicide is one of the leading causes of death globally. Suicide is the second leading cause of death after cardiovascular disease, cancer, and road traffic accidents. It is also the most common cause of death among young people and the working-age population worldwide. According to WHO, approximately 800,000 people commit suicide every year worldwide. This equates to one person committing suicide every 40 seconds. An estimated 4 million people may have committed suicide in the past 5 years. Suicide is the leading cause of death in high-income countries. 79% of suicides occur in low- and middle-income countries. Among adolescents aged 15–19, suicide is the third leading cause of death worldwide. According to WHO 2023, suicide is one of the top 10 causes of death worldwide. Among 15-29-year-olds, it is among the top 4 main causes of death. To reduce the number of suicides, WHO recommends a number of measures, including data collection and monitoring, organizing activities in educational institutions, reducing the consumption of alcohol and drugs among the population, training medical workers, etc. This information presents the results of the autopsy analysis conducted in suicide cases at the Andijan branch of the Republican Scientific and Practical Center for Forensic Medical Examination in 2024. In 2024, the population of the region reached 3,300,000, of which 0.003% of the total population died by suicide. During the year, a total of 117 suicide cases were recorded. Most of them died by suicide. Two-thirds of the cases were men. By territory, they were more common in the Shahrikhan (75%) and Andijan (25%) districts of the region than in other districts
Keywords: autopsy; self-murder; suicide